Examining the Determinants of Consumers’ Purchase Behaviour: Green Packaging Products - Goh Mei Ling; Ho Sew Tiep; Yeo Sook Fern; Teh Wei Lun (Research Synergy Foundation, 2022)
Disposal of plastic packaging has caused the increase of amount of waste. The non-biodegradeble plastic packaging will pollute the environment and its toxic chemical will have adverse effects to our health. One of the ways to minimise the plastic waste is to use the green packaging. Green packaging is eco-friendly packaging, harmless to human health and more importantly it is biodegradable. Many businesses have switched to going green concepts by providing green products and services. Therefore, the objective of this study is to examine the determinants of consumers’ purchase behaviour from the perspective of green packaging products. This study has recruited 200 respondents from Melaka using convenience samping. Survey was used for data collection with a set of self-administered quesntionnaires that covered respondents’ demographic background and all the variables in the research model. PLS-SEM was used to examine the validity and relationships of the constructs. Both convergent validity and discriminant validity were deemed satisfactory. 0.444 of R2 was obtained from the data analysis. This means that the model explained 44.4% of total variation of purchase behaviour. Environmental concern and environmental attitude were found positively affect consumers’ purchase behaviour towards green packaging products. Environmental knowledge and social influence, however, were found to have no effect on the purchase behaviour. This study will be able to provide valuable information to the marketers to focus not only on their products but the packaging of their products as well. This study also provides an insight into the consumers’ purchase behaviour towards green packaging products. It is recommended to future research to recruit more respondents with more diversify background and include other variables.